Pengaruh Kepuasan Komunikasi Organisasi Terhadap Kinerja Pegawai Di Sekretariat DPRD Kota Singkawang - Triyono, Agus; Riyantini, Kurnia (Informasi, 2016)
In an effort to achieve a success, then the satisfaction of organizational communication is a very important factor, it "˜caused communication satisfaction is the result of a number of processes that are internal and external.Employees is one of the most important assets who participate in helping in the achievement effortof organizational goals that is realization of the vision and mission of the organization. Therefore, good cooperation between the organization and all employees are indispensable so that common goals can be realized. This research aims to find the influence of communication organizational satisfaction to employees performance in Secretariat Legislature Singkawang city. This research uses quantitative research, the method used in this research is survey method. In this research, researcher used a questionnaire as the data collection technique. Sample in this study is all civil servants in Secretariat Legislature Singkawang city numbered as many as 35 people. Data analysis techniques used in this study is simple linear regression analysis techniques. Based on the results of simple linear regression test, obtained constant values from the regression variable employees performance that is equal 26,603. While the regression coefficient of the variable communication organization satisfaction is positive that is equal 0,462. This means that the variable communication organization satisfaction have a positive influence on variable employees performance that is equal 0,462. Based on t-test result, obtained t value of 3,874, greater than the table value of 2,034. Therefore, it can be concluded that H0rejected. This mean that the amount of significant influence among the variables communication organization satisfaction to employees performance of 31,3% while the rest 68,7% influenced by other variable.